FUNCTIONAL CAPABILITIES OF THE DESIGN OF VIRTUAL LABS - Бегалин, А.Ш.; Лифенко, В.М. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2013)
In work results of researches in the field of creation of electronic virtual laboratory by means of the visual environment of programming are offered, questions of integration of various tools for creation of the designer of such training systems are considered. Attempt of creation of the universal and multipurpose program considering level of initial knowledge of trainees is made.
Keywords: virtual lab; programme; designer of learning systems; multimedia; data encryption; decryption; catalog